Inclusive landscape management: a guide for process facilitators - International Water Management Institute (International Water Management Institute, 2025)
The Inclusive Landscape Management Facilitators’ Manual is a comprehensive guide for co-designing and implementing sustainable landscape plans. It is a practical toolkit that provides a flexible, step-by-step approach for bringing diverse stakeholders together to negotiate and act on shared priorities. The manual is structured into four sequential phases: project preparation, situational analysis, plan development, and implementation. It emphasizes inclusivity by embedding gender equality, social inclusion, and youth engagement. By linking these processes to governance structures and policies, it aims to institutionalize learning and collaboration. The guide positions ILM as a strategic tool to address critical challenges such as food security, climate resilience, and biodiversity. While acknowledging implementation challenges like limited capacity and resource constraints, it stresses the importance of capacity development and partnerships. Ultimately, this manual is a strategic framework for creating resilient, long-term landscape governance systems that benefit people, ecosystems, and economies.